(untitled) (African Human Mobility Review, 2021)
This research empirically examines the macroeconomic determinants of â€˜pullâ€™ factors of international migration in South Africa. Using the neoclassical economic model of international migration, an Ordinary Least Square (OLS) regression was run on time-series data from the World Bank data base for the period 1990-2012. Relevant data from the South African Department of Home Affairsâ€™ Annual Reports were also used. GDP per capita, inflation rate, real interest rate, employment rate and public health expenditure were found to be the key determinants which entice migrants away from their countries and direct them to â€œbetter offâ€ destinations. The countryâ€™s public education system, on the other hand, is not a significant attraction for foreign migrants. The study concludes that the South African government urgently needs to implement not only skilled worker-attractive immigration policies but also appropriate fiscal and monetary restructuring policies aimed at growing the economy and creating employment opportunities.